Formation of nano-crystalline phase in hydrogenated amorphous silicon thin film by plasma focus ion beam irradiation - Ngoi, S.K.; Yap, S.L.; Goh, B.T.; Ritikos, R.; Rahman, S.A.; Wong, C.S. (2012)
A 3.3 kJ Mather type dense plasma focus device is used to generate a pulsed argon ion beam of 100 KeV in this work. Hydrogenated amorphous silicon (a-Si:H) film prepared by plasma enhanced chemical vapor deposition (PECVD) on c-Si substrate was irradiated with the argon ion beam produced by this dense plasma focus device. The effects of exposure to a single, 5 and 10 shots of dense plasma focus argon ion beam irradiation on the surface morphology, crystallinity and chemical bonding properties of the a-Si:H films were studied using Field Emission Scanning Electron Microscope (FESEM), X-ray Diffraction (XRD), Raman scattering and Fourier Transform Infrared (FTIR) spectroscopy, respectively. Formation of nano-crystalline silicon phase along with increase in structural order and hydrogen content in the film structure has been observed when the a-Si:H film was irradiated with a single shot of dense plasma focus argon ion beam. Exposure to 5 and 10 shots of the dense plasma focus argon ion beam irradiation reduced the hydrogen content resulting in a decrease in crystallinity and structural order in the film structure.